2015
DOI: 10.1134/s107042801504003x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-(adamantan-1-yl)amides by reaction of carboxylic acid amides with 1-bromo(chloro)adamantane catalyzed by manganese compounds

Abstract: N-(Adamantan-1-yl)amides were synthesized in 70-90% yield by reaction of 1-bromoadamantane with carboxylic acid amides in the presence of manganese salts and complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Along with well-known and comprehensively studied adamantyl-containing amines, amantadine and rimantadine, antiviral activity has been found for adamantylated azoles, amides, sulfamides, urethanes, and some other types of compounds. In addition, adamantylated nitrogencontaining compounds are of interest as intermediates for the synthesis of other compounds with practically valuable properties.The known methods for the preparation of these compounds consist in adamantylation of various N-nucleophiles with adamantane, 1-haloadamantanes, or 1-adamantanol in the presence of Lewis or Brønsted acid, i.e., under conditions favoring the formation of 1-adamantyl cation.For example, N-adamantylation of amides was proposed to be carried out using manganese catalysts (Figure 1), among which dimanganesedecacarbonyl showed the best results to give target compounds in a yield up to 94% [2]. In the trifluoroacetic acid medium (Figure 2), the adamantylation of carboxylic acid amides can be carried out with different efficiency upon long-term reflux [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Along with well-known and comprehensively studied adamantyl-containing amines, amantadine and rimantadine, antiviral activity has been found for adamantylated azoles, amides, sulfamides, urethanes, and some other types of compounds. In addition, adamantylated nitrogencontaining compounds are of interest as intermediates for the synthesis of other compounds with practically valuable properties.The known methods for the preparation of these compounds consist in adamantylation of various N-nucleophiles with adamantane, 1-haloadamantanes, or 1-adamantanol in the presence of Lewis or Brønsted acid, i.e., under conditions favoring the formation of 1-adamantyl cation.For example, N-adamantylation of amides was proposed to be carried out using manganese catalysts (Figure 1), among which dimanganesedecacarbonyl showed the best results to give target compounds in a yield up to 94% [2]. In the trifluoroacetic acid medium (Figure 2), the adamantylation of carboxylic acid amides can be carried out with different efficiency upon long-term reflux [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that the Mn-catalyzed reaction of 1-bromoadamantane with carboxylic acid amides produced N-(adamantan-1-yl)amides in yields of 70-90% [10].…”
mentioning
confidence: 99%
“…The reactions were carried out as described previously [10]. The interaction of 1-bromo-3,5-dimethyladamantane I with formamide, acetamide, propionamide, and benzamide in the presence of Mn 2 (СО) 10 [or MnCl 2 , MnBr 2 , Mn(OAc) 2 , Mn(acac) 3 ] resulted in the formation of the corresponding N-(3,5-dimethyladamant-1-yl)amides II-V in 78-99% yield. At the same time the nature and the structure of the organic amide had no significant effect on the selectivity of the reaction and the yield of adamantylamide (Scheme 1).…”
mentioning
confidence: 99%